2013
DOI: 10.5688/ajpe77110
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Pharmacogenomics Educational Program for Pharmacists

Abstract: Objectives. To evaluate hospital and outpatient pharmacists' pharmacogenomics knowledge before and 2 months after participating in a targeted, case-based pharmacogenomics continuing education program. Design. As part of a continuing education program accredited by the Accreditation Council for Pharmacy Education (ACPE), pharmacists were provided with a fundamental pharmacogenomics education program.Evaluation. An 11-question, multiple-choice, electronic survey instrument was distributed to 272 eligible pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 22 publications
1
52
0
Order By: Relevance
“…Others have researched pharmacogenetic education [30,31] and set pharmacogenetic educational stan- Our approach demonstrated that a single 1-h pharmacogenetic seminar, conducted by a pharmacist during an existing education time (grand rounds continuing medical education), can still effectively change physicians' attitudes. However, the difference in educational intensity between our study and the study by Owusu-Obeng et al probably reflects the educational intensity required to change action, and not just attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Others have researched pharmacogenetic education [30,31] and set pharmacogenetic educational stan- Our approach demonstrated that a single 1-h pharmacogenetic seminar, conducted by a pharmacist during an existing education time (grand rounds continuing medical education), can still effectively change physicians' attitudes. However, the difference in educational intensity between our study and the study by Owusu-Obeng et al probably reflects the educational intensity required to change action, and not just attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…A report of an ACPE program demonstrated some improvement in pharmacists' knowledge of PGx, but still a relatively low knowledge level following the completion of the program (precourse score: 46%; postcourse score: 53%) [19]. Therefore, it may be necessary to expand the introductory homestudy modules with more detailed optional modules about the history of PGx, understanding genetic variation, clinical PGx evidence and drug-gene interactions.…”
Section: Ce 2 Years After the Completion Of Course (Estimated Time Tomentioning
confidence: 99%
“…Although they have acknowledged their limited knowledge of this field [6,18] and need for further training to increase their confidence in providing PGx testing [7,19,20], there are few data that specify the content of PGx education for pharmacists. Romagnoli et al [21] categorized 36 informational needs into four broad categories based on pharmacist interviews: background; specific medication and drug-gene details; patient-specific clinical information; and PGx guidance-related information.…”
mentioning
confidence: 99%
“…6 Similarly, some pharmacy students feel that exercises involving the direct application of genetic data to drug therapy would increase their comfort level with interpreting and applying pharmacogenetic test results. 4 Participation on a clinical pharmacogenetics service would provide pharmacy students, residents, and fellows with firsthand experience with interpreting and applying genetic information to drug management.…”
Section: Introductionmentioning
confidence: 99%
“…5 An intensive educational effort would probably be necessary to improve pharmacists' knowledge and comfort level with pharmacogenetics, and a continuing education program alone, without hands-on experience probably would be insufficient. 6 Similarly, some pharmacy students feel that exercises involving the direct application of genetic data to drug therapy would increase their comfort level with interpreting and applying pharmacogenetic test results. 4 Participation on a clinical pharmacogenetics service would provide pharmacy students, residents, and fellows with firsthand experience with interpreting and applying genetic information to drug management.…”
Section: Introductionmentioning
confidence: 99%